Home Literacy Environment and Domain-Specific Early English Literacy Outcomes in a Multilingual Context - Zakaria, Noor Asma Iffah; Md. Nor, Mariani (Universitas Negeri Padang, 2026)
This paper reports findings from one component of a larger research project examining ecological influences on early English literacy development among Malaysian preschool children. Grounded in Bronfenbrenner’s bioecological theory and Ajzen’s theory of planned behaviour, the study investigates how multiple dimensions of the home literacy environment (HLE): parents’ literacy beliefs, parents’ literacy habits, parent–child literacy interactions, and frequency of English use at home, are associated with children’s early English literacy outcomes. Participants comprised 207 preschool children aged five to six years, their parents from registered preschools in urban districts of Selangor, Malaysia. Data were collected using a parent-report HLE survey and a standardized early English literacy assessment battery measuring English decoding skills and expressive English vocabulary. Findings revealed hierarchical and domain-specific relationships among the constructs. Parent–child literacy interaction and frequency of English use at home were directly associated with children’s English vocabulary knowledge, while parents’ literacy beliefs and literacy habits exerted significant indirect effects through literacy interactions. No direct association was found between HLE variables and children’s English decoding skills. English vocabulary, however, was strongly associated with decoding, suggesting interrelated but distinct developmental pathways. The findings extend existing HLE models by explicating belief–practice–outcome mechanisms in a multilingual English as a second language (ESL) context and by highlighting the differential roles of home influences in early English literacy development.